Acute Obstructive Abdomen Due to Gallstone Ileus: Case Report and Literature Review - Grenteski, Fabricio; Lopes, Laura Mendes; Cavalheiro, Gabriel Rodrigo; Costa, Gustavo Henrique Morcelli da; Naufel Júnior, Carlos Roberto; Coelho, Guilherme de Andrade; Ferrarini, Guilherme; Peixoto, Igor Luna; Feitoza, José Anderson (Brazilian Journal of Case Reports, 2024)
Gallstone Ileus is a rare complication of cholelithiasis and one of the rarest forms of mechanical intestinal obstruction. It occurs in 0.3% to 0.5% of patients with cholelithiasis and is responsible for 1% to 4% of cases of mechanical obstruction. It is caused by the impaction of gallstones in the gastrointestinal tract after passing through biliary-enteric fistulas. The diagnosis is often delayed or missed due to the non-specificity of symptoms, leading to a reserved prognosis with high mortality and morbidity rates. Although the treatment and management of gallstone ileus remain controversial, the primary therapeutic goal is the extraction of the stone through a surgical approach. This case aims to describe a rare instance of intestinal obstruction due to gallstone ileus, where the stone was eliminated with clinical measures combined with surgery to correct a choledochoduodenal fistula.